Between Public and Communal Interests: A Legality Issue Forced Evictions Occuring in Jakarta - Kusumawati, Erna Dyah (UI Scholars Hub, 2018)
Forced evictions are considered as a “global epidemic” since they occur in several countries regardless of the states’ development level. The private ownership issues and the development issues are examples of rationales behind forced evictions. Under the human rights regime, states are obliged to refrain from any eviction, moreover, the states are required to adopt measures preventing forced evictions from happening or provide the victims with legal mechanisms to challenge the policies if evictions occur. International law prohibits forced evictions and offers a guideline for forced eviction triggered by development. This paper will investigate the legality of forced evictions happening in Jakarta, Indonesia and critically examine the reason of “public interest” proffered by the authorities as to whether the forced evictions are in contrary to the international obligations to which Indonesia has subscribed or whether it can be justified by the wider public interests reasoning. The author argues that in the name of development, a conflict of interests between a larger public interest and the interest of the evicted community may occur. Since forced evictions are associated with violations of human rights, especially the right to adequate housing, therefore the interests of both public and community should be given more attention particularly if forced evictions cannot be avoided.